Nursing care gestion of chronically ill elderly people. Policlinico 2, year 2007 - Liudmila Carbonell Sanamé (Fundación para el Desarrollo de la Enfermería, 2009)
A descriptive prospective study was made to those patients aged more than 60 years who are attended in the Policlinico 2 "Leonilda Tamayo Matos" in Isla de la Juventud during the year 2007. The study population was 1254 and 700 chronically ill elderly people were taken as representative sample, using a simple random sampling. The Mini Mental State Examination and a satisfaction survey was made to old people, all these with their informed consent. The main variables to study were: sex, age, race, civil state, educational level, work, assistance to the Grandparent's Circle and satisfaction level. There exists a feminine predominance (61%) over male, as well as the age group from 60 to 64 years old. Mixed race is the most common one (43%), followed by black (35%). 43% of these elders have secondary studies, and 64% of them are retired. The assistance to the Grandparent's Circle is good, 338 of all the elders studied (48.2%) assist to it. The results were expressed with real numbers and percentages, and were represented in bar and pie charts. There exists a predominance of arterial hypertension and diabetes mellitus in the elders studied. The quality of the nursing cares to the chronically ill old people of the policlinic 2 in 2007 was good.